Deciphering the mechanism of Annona muricata leaf extract in alloxan-nicotinamide-induced diabetic rat model with 1H-NMR-based metabolomics approach - Zubaidi, Siti Norliyana; Wong, Pei Lou; Qadi, Wasim S.M.; Dawoud, Esraa Adnan Dawoud; Hamezah, Hamizah Shahirah; Baharum, Syarul Nataqain; Jam, Faidruz Azura; Abas, Faridah; Moreno, Andres; Mediani, Ahmed (Elsevier, 2025)
The leaves of Annona muricata Linn. have long been utilized in traditional medicine for diabetes treatment, and there is no study that has employed a metabolomics approach to investigate the plant's effects in managing the disease. We aimed to explore the antidiabetic effects of the standardised A. muricata leaf extract on diabetes-induced rats by alloxan monohydrate (Ax) and nicotinamide (NA) using a proton nuclear magnetic resonance (¹H-NMR)-based metabolomics approach. Absolute quantification was performed on the leaf extract using ultra-high-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS). Two different doses of the extract were administered orally for four weeks to diabetic rats induced with Ax + NA, and physical evaluations, biochemical analyses, and ¹H-NMR metabolomics of urine and serum were assessed. The results showed that quercetin 3-rutinoside was the most abundant compound in the 80 % ethanolic extract of A. muricata leaf. The induction of type 2 diabetes mellitus (T2DM) in the rat model was confirmed by the clear metabolic distinction between normal rats, diabetic rats, and metformin-treated diabetic rats. The low-dose of A. muricata leaf extract (200 mg/kg) was found to exhibit better results, significantly reducing serum urea levels in diabetic rats, with effects comparable to those of metformin. Additionally, metabolite analysis from ¹H-NMR metabolomics of serum and urine showed a slight shift toward normal metabolic profiles in the treated diabetic rats. Pathway analysis revealed alterations in the tricarboxylic acid cycle (TCA), pyruvate metabolism, and glycolysis/gluconeogenesis pathways in the diabetic rat model, which were improved following treatment with the A. muricata leaf extract. Overall, this study provides scientific support for its traditional use in diabetes management and offers new insights into the underlying molecular mechanisms.